Clinical Guidelines on the Use of Assisted Reproductive Technology During Covid-19 Pandemic: A Minireview of the Current Literature - Soudabeh Sabetian; Bahia Namavar Jahromi; Farnia Feiz; Isabella Castiglioni; Claudia Cava; Sina Vakili (Shiraz University of Medical Sciences, 2022)
Background: The coronavirus disease-2019 (COVID-19), caused by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is now spread  worldwide. Therefore, informative and reliable data related to the exact effects of COVID-19 on fertility and pregnancy is still of great interest until the pandemic is declared over. General guidelines regarding the protection and management of COVID-19 have been published and new information will continue to be updated daily. Methods: In this review, we summarized clinical health guidelines for reproductive and infertility centers to improve quality management in assisted reproductive technology and minimize the potentially harmful consequences of COVID-19 on pregnancy and fertility. Results: As specified in the literature, protocols consist of five categories, including protocols for couples, protocols for women, protocols for men, labor and delivery, and postpartum and breastfeeding. Conclusion: General protocols for patients and staff may vary depending on specific conditions. However, this review provides some rules to ensure their safety against the disease during the pandemic.